Analysis of pH and cytotoxic activity of locally produced radiopaque white Portland cement - Fen, Soh Chin; Lek, Loh Wei; Kannan, Thirumulu Ponnuraj; Abdullah, Siti Fadilah Bin; Husein, Adam; Nabhan, Mohamed Shady; Ahmed, Hany Mohamed Aly (European Journal of General Dentistry, 2018)
Background: Portland cement (PC)-based formulations show continuous developments. Purpose: This study examined the pH and cytotoxic activity of a locally produced Malaysian white PC (MAWPC) mixed with different radiopacifying agents (barium sulfate [BS], niobium oxide [NO], and bismuth oxide [BO]) on human periodontal ligament fibroblasts (HPLFs). Materials and Methods: 0.8 g of MAWPC was mixed with 0.2 g of each radiopacifying agent and sterile distilled water. Five tablets of each group were prepared. After setting, the samples were immersed in 10-ml sterile distilled water and stored at 37°C, and the pH was measured at intervals of 0, 1, 3, 7, and 14 days using a calibrated digital pH meter. One-way ANOVA was used for data analysis (P = 0.05). For cytotoxic activity, the material extracts were prepared at three serial concentrations (25, 12.5, and 6.25 mg/ml), and 200 ml of each concentration was added into each well seeded with cultured HPLFs. The plates were then incubated for 48 h. The cell viability was evaluated using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay, and the data were analyzed using Kruskal–Wallis test (P = 0.05) Results: The pH values of all groups were significantly higher compared to the control group (P < 0.001). With the exception of day 0, the pH values of all groups at all day intervals ranged from 9.9 to 10.9, and some significant differences were detected. Although the addition of radiopacifying agents decreased the cell viability values of MAWPC extracts (P < 0.05), all groups showed favorable cytotoxicity profile. MAWPC/BO combination showed higher cell viability values compared to MAWPC/NO and MAWPC/BS. Conclusions: The addition of radiopacifying agents to MAWPC maintained its high pH and favored the viability of HPLFs.
Keywords: Barium sulfate; bismuth oxide; cell viability; cytotoxicity; human periodontal ligament fibroblasts; niobium oxide; pH value; Portland cement